Evaluation of the necessity of laparoscopic repair of a uterine scar defect for cesarean scar pregnancy. Issue 1 (January 2022) - Xiang, Jiangdong; Cao, Yannan; Zhou, Lina; Yang, Haiying; Wu, Sufang; Li, Linxia
Objective: This study aimed to determine the risk factors associated with the necessity of laparoscopic scar defect repair for cesarean scar pregnancy (CSP). Methods: We retrospectively analyzed 237 patients with CSP who were treated by ultrasound-guided suction curettage and/or laparoscopy in our hospital from April 2012 to November 2019. A total of 199 of these patients underwent ultrasound-guided suction curettage without uterine scar defect repair, while 38 of these patients underwent laparoscopic resection and uterine scar defect repair. We analyzed various clinical variables and compared the efficacy of treatment between the two groups. Results: Gestational age, the maximum transverse diameter (MTD) of the gestational sac, myometrial thickness, the operation time, intraoperative blood loss, and the duration of the hospital stay were significantly different between the two groups. Gestational age, the MTD of the gestational sac, and myometrial thickness were independent risk factors for laparoscopic repair. Conclusions: Gestational age, the MTD of the gestational sac, and myometrial thickness are important factors associated with the necessity for laparoscopic repair of a uterine scar defect.